Ordem, perigo e prisão : uma análise da categoria ordem pública como requisito para a decretação da prisão prevensão - Britto, Jeiko Leal Melo Hohmann (2022)
The formation of the authoritarian structure of our criminal procedural legislation dates back to the Italy of Arturo Rocco and Vicenzo Manzini, precursors and ideologues of the 1930’s facist code of Italian criminal procedure. Written by a commission of jurists and under the baton of the then minister Francisco Campos, in the midst of Vargas ‘Estado Novo’. The ideologues of the ‘Estado Novo’ defended the strong state, commanded by ruling elites and technocrats based on scientific knowledge of social sciences, notably sociology, in order to overcome the crisis caused by political liberalism. This ideology is updated in the 50s and 60s of last century and remains alive in the midst of a democratic regime, permeating the criminal process by keeping the inquisitorial system alive; thus reducing the scope of protection of the right to freedom, notably by the generalized use of preventive detention, which has, to a large extent, the maintenance of public order as the basis of the precautionary measure. Confirming this situation, data form the National Council of Justice – NCJ show that Brazil currently has 905,369 peaple in prision, of which 403,083 are provesional prisoners and 193,507 are serving a provisional sentence. Thus, the investigation of the public order category as a pre-trial detention requirement aims to uncover what this category serves in the criminal procedural scope, its (non)conformity with the 1988 Constitution and functionality to the criminal justice system. This analysis involves the study of the type of political regime in force at the origin of the Brazilian Code, as well as the theoretical sources that served as the basis for its elaboration, as well as its permanence over more than 8 decades of validit.